Municipal finance and resilience lessons for urban infrastructure management: a case study from the Cape Town drought. Issue 3 (2nd September 2019) - Simpson, Nicholas Philip; Simpson, Kayleen Jeanne; Shearing, Clifford D.; Cirolia, Liza Rose
ABSTRACT: At a time when flows of both water and finances were severely curtailed, this article explores the public and private adaptation actions which played out during Cape Town's drought which produced a 'shock within a shock' on the municipality's budget (2016–2018), this article provides a detailed and embedded account of the severity, urgency and complexity of the challenges that decision makers are faced with during such unanticipated events. Shifts in approaches are identified and traced through budget allocations to display uncharted governance arrangements which, although stabilising, present novel finance and governance challenges amidst altered resource and operating conditions. Reflecting on observed shifts and shock to the municipal budget, the article highlights the challenge of an uncoordinated response between public and private actors that aim to secure high-reliability service delivery. Reflecting on the findings, recommendations outline resilience qualities necessary to municipal budgets through sketching contextually reflective questions for municipal financing models.